Pilar Kekuasaan Turki Utsmani: Dinamika Administrasi dan Pemerintahan yang Cemerlang - Ar-Rafi, Najjana Hamim; Rossy, Mahmud Ibnu; Virmansyah, Muhammad Dava; Ahmad, Sahal; Fahmi, Faiz Fikri Al (Intitut Agama Islam Nasional Laa Roiba Bogor, 2025)
Ottoman Turkiye was one of the strongest empires in history, which reached the peak of glory thanks to a brilliant system of government and administration. This article examines the dynamics of administration and governance of the Ottoman Turkish government which became the foundation of its power for more than six centuries. The main focus of this research is the analysis of bureaucratic structure, the central role of the Sultan, the function of the Imperial Council (Divan), and the integration of Islamic law in the political and social system. In addition, this article reviews the Jenissari-based military system and management of conquered territories that contributed to the stability of the empire. A multidisciplinary approach is used to highlight the relationship between government policies and the socio-economic dynamics of Ottoman Turkish society. The research results show that the success of the empire did not only lie in military strength, but also in administrative efficiency that was adaptive to the challenges of the times. By highlighting this administrative legacy, this article offers a new perspective for the study of modern governance, including the values of justice, sustainability and inclusiveness that are still relevant today. This study aims to enrich the literature on Islamic history and inspire governance approaches in the contemporary era.